2014
DOI: 10.1371/journal.pone.0111062
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Salmonella OmpD Porin in the Infection of RAW264.7 Macrophages and BALB/c Mice

Abstract: Salmonella Typhimurium is the etiological agent of gastroenteritis in humans and enteric fever in mice. Inside these hosts, Salmonella must overcome hostile conditions to develop a successful infection, a process in which the levels of porins may be critical. Herein, the role of the Salmonella Typhimurium porin OmpD in the infection process was assessed for adherence, invasion and proliferation in RAW264.7 mouse macrophages and in BALB/c mice. In cultured macrophages, a ΔompD strain exhibited increased invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…Hence, the downregulation of ompD could be another factor for the reduction of adhesion and invasion of Salmonella Typhimurium in mammalian cells. This is concurrent with the findings of Ipinza et al [38] who described the role of ompD in Salmonella invasion and intracellular survival in RAW264.7 cells and BALBc mice. The significance of ompD in adherence of Salmonella Typhimurium was also indicated in human monocytes and intestinal epithelial cells [39].…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the downregulation of ompD could be another factor for the reduction of adhesion and invasion of Salmonella Typhimurium in mammalian cells. This is concurrent with the findings of Ipinza et al [38] who described the role of ompD in Salmonella invasion and intracellular survival in RAW264.7 cells and BALBc mice. The significance of ompD in adherence of Salmonella Typhimurium was also indicated in human monocytes and intestinal epithelial cells [39].…”
Section: Discussionsupporting
confidence: 91%
“…Expression of nmpC was downregulated in S. Typhimurium exposed to H 2 O 2 (Calderón et al, 2011). Additionally, NmpC may be needed for adherence and recognition of S. Typhimurium to human macrophages and epithelial cells during the initial stages of infection (Hara-Kaonga and Pistole, 2004) and is also involved in host cell recognition in mammalian models (Ipinza et al, 2014;van der Heijden et al, 2016). In our study, we observed up-regulation of both nmpC and ROS detoxification gene ahpC on leaves.…”
Section: Discussionsupporting
confidence: 53%
“…In mice immunized with porins (containing mainly OmpD), IgM antibodies are produced by B1b cells and these antibodies reduce S. typhimurium bacteraemia, suggesting a protective role for OmpD . In RAW264.7, a mouse macrophage cell line, OmpD inhibits replication of S. typhimurium and reduces systemic dissemination by neutralizing reactive oxygen species .…”
Section: Discussionmentioning
confidence: 99%